Virtual Topography: Poets, Painters, Publishers and the Reproduction of the Landscape in the Early Nineteenth Century - Fulford, Tim (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2010)
In this article I develop the work of a number of critics—Gillen Darcy Wood, Sophie Thomas, Peter Simonsen, Julia S. Carlson—who have recently begun to revise our understanding of the relationship of literary Romanticism, and in particular that of Wordsworth and Southey, to visual culture. I show first that new means of mechanical reproduction—the woodcut, the aquatint—combined with technological changes in book production, stimulated a new print genre known as Views—an ancestor of the coffee-table book and often a spin-off wherein the public could see engravings of the scenes their favourite landscape poets described. Pictures sold poets, and, for the first time in history, popular writers were marketed to a mass readership able—and avid—to buy images as well as words. Wordsworth and Southey were not popular writers and were not at first marketed as illustrated poets. And they at first disapproved of the visual turn of their culture. This disapproval, I show, was never consistent or total and in fact they strove to take advantage of the vogue for the visual, collaborating with artists to publish volumes of Views in which their writing was combined with engravings of landscape. And these collaborations, I argue, were greatly influential upon them, causing them to alter the form and style of their writing as well as the publication formats in which it appeared. Wordsworth and Southey, in their late work, became writers of a moralised picturesque—of words that deferred to pictured views and tourist sights—and that sought to derive truths about human nature, life and society from them. Departing from their earlier suspicion of the visual, and of Views, they became practitioners, in conjunction with artists, of a virtual topography. Their continued marketing, in the 21st century, as part of the visual packaging of the Lake District in picture-book, DVD, and website is therefore not as contrary to what they stood for as it first might seem, shallow though it often is.